Melania and me [compact disc, unabridged] : the rise and fall of my friendship with the First Lady - Wolkoff, Stephanie Winston, 1971- (Simon & Schuster Audio, 2020)
In this candid and emotional memoir, Stephanie Winston Wolkoff takes you into Trump Tower and the White House to tell the funny, thrilling, and heartbreaking story of her intimate friendship with one of the most famous women in the world, a woman few people truly understand.